Guarding the Political Assembly : The Reasons and Assesing Impeachment Clause in Indonesia - Rishan, Idul; Pratiwi, Dian Kus (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 1 (2023), 2023)
In deliberative democracy, a constitution provides formal procedures for discharging the president and/or vice president during his/her term of office This research aims to reveal two things. First, the reasons why discharging the president or vice president during his/her term of office is more political than legal. Second, assessment of provisions on discharging the president and/or vice president during his/her term of office. This is a doctrinal legal research using secondary data, and analyzed by the method of statutory approach, historical method, and conceptual method. This study has found that the political forum in MPR cannnot be separated from the presidential system, characterized by political and government stability. Therefore, bipartisan decision making in MPR needs strengthening. However, DPR has unwittingly acted as prosecutors as well as justices at the MPR level. In addition, the provisions of Articles 7A-8 of the constitution should be stipulated further.